Pengaruh Pemahaman Investasi dan Pelatihan Pasar Modal terhadap Minat Investasi Mahasiswa di Pasar Modal Syariah dengan Motivasi sebagai Variabel Intervening - Deksa Imam Suhada; Andri Soemitra; Rahmat Daim Harahap (MES Bogor, 2023)
The capital market is one of the indicators in improving the economy of a country. With the rapid development of the capital market and can be used as an alternative to invest for students of the Islamic Economics study program at UIN North Sumatra. This study aims to determine the effect of understanding investment and capital market training on student investment interest in the Islamic capital market and to determine the effect of understanding investment and capital market training on student investment interest in the Islamic capital market through motivation. The population in this study was 806 with a sample of 230 students. The results of this study indicate that the exogenous variables of understanding investment, capital market training and motivation have an effect on student investment interest in a combined manner with a coefficient of determination (R2) of 51.7% in sub structure I. Exogenous variables of understanding investment and capital market training have an effect on motivation. combined with the coefficient of determination (R2) of 47.0% in sub structure II. It is hereby stated that investment understanding and capital market training have an effect on investment interest with motivation as an intervening variable. Keywords : Investment, Capital Market Training, Investment Interest